Improvement in Hardness of LM-6 Aluminum Alloy Green Sand Castings by Taguchi Method - Kumar, Ravneet; Grewal, Chandandeep (Asian Journal of Engineering and Applied Technology, 2013)
The green sand casting is most widely and economically used method for past years. The quality of castings and parameters control is very important. With increasing demand for high-quality castings with close tolerances, an attempt has been made in this study to get the optimal setting of the main parameters to improve the hardness of LM-6 Aluminum alloys castings in green sand casting. Five main parameters namely Bentonite clay, Grain fineness no., Moisture, Pouring temperature and Coal dust were identified. The effects of the selected process parameters on the hardness and the subsequent optimal settings of the parameters have been accomplished using Taguchi’s method. L8 (27) orthogonal arrays have been selected and experiments were conducted as per experimental plan given in this array. The results indicate that all the parameters except grain fineness no and coal dust are affecting both the average and variability significantly in the hardness of LM-6 Aluminum alloys castings. The confirmatory experiments have shown improvement in Rockwell hardness to be 6.9%.